The Power of a Profound Experience With Nature: Living With Meaning - Mathers, Becky; Brymer, Eric (Frontiers in Psychology, 2022)
Nature based experiences have been linked to significant positive outcomes for people and the planet. Significant life experience research investigates the associations between formative experiences in nature and resulting environmental concern and action, including both singular events and repeated experiences. However, little is known about the long-term impacts of singular profound experiences with nature. This study used a semi-structured interview guide with twenty-one adults who had a profound experience with nature. Three themes resulted from the thematic analysis process: 1) Living in relation with nature, 2) Living authentically, and 3) Living a meaningful life. The findings demonstrate that a single profound experience with nature can have long lasting and significant effects on an individual. Understanding these long-term influences and uses of a profound experience with nature have implications for intervention designers such as health practitioners and environmental educators, as well as policy makers.